Pengaruh Keterikatan Kerja, Lingkungan Kerja, dan Pembelajaran Organisasi terhadap Komitmen Organisasi di Puskesmas Nawangan - Devi Prastika; Dorothea Wahyu Ariani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This research aims to analyze the influence of work engagement, work environment, and organizational learning on organizational commitment at the Nawangan Community Health Center. The sample in this study was 50 respondents who worked at the Nawangan Community Health Center. The data collection technique used was a survey method with the research instrument used was a questionnaire. The results of the instrument test stated that the data in this study was proven to be valid and reliable. The Classical Assumption Test states that the data in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The results of this research prove that: (1) Work Engagement has a positive and significant effect on Organizational Commitment, (2), Work Environment has a positive and significant effect on Organizational Commitment, (3) Organizational Learning has a positive and significant effect on Organizational Commitment